1996
DOI: 10.1289/ehp.96104728
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mortality and cancer incidence among alachlor manufacturing workers.

Abstract: Alachlor is the active ingredient in a family of preemergence herbicides. We assessed mortality rates from 1968 to 1993 and cancer incidence rates from 1969 to 1993 for manufacturing workers with potential alachlor exposure. For workers judged to have high alachlor exposure, mortality from all causes combined was lower than expected [23 observed, standardized mortality ratio (SMR) = 0.7, 95% CI, 0.4-1.0], cancer mortality was similar to expected (6 observed, SMR = 0.7, 95% CI, 0.3-1.6), and there were no cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 3 publications
0
24
1
Order By: Relevance
“…Burns (2005) studied cancer rates among manufacturing workers and applicators and found that cancer risk was not increased among these groups. Of the studies reviewed by Burns that reported results for prostate cancer, none observed a statistically significant increase in risk (Axelson et al, 1980;Ott et al, 1980;Wong et al, 1984;Swaen et al, 1992;Bas Bueno de Mesquita et al, 1993;Acquavella et al, 1996;Helgesen et al, 1996;Sathiakumar et al, 1996;Kogevinas et al, 1997;Zahm, 1997;Lynge, 1998;Burns et al, 2001;MacLennan et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Burns (2005) studied cancer rates among manufacturing workers and applicators and found that cancer risk was not increased among these groups. Of the studies reviewed by Burns that reported results for prostate cancer, none observed a statistically significant increase in risk (Axelson et al, 1980;Ott et al, 1980;Wong et al, 1984;Swaen et al, 1992;Bas Bueno de Mesquita et al, 1993;Acquavella et al, 1996;Helgesen et al, 1996;Sathiakumar et al, 1996;Kogevinas et al, 1997;Zahm, 1997;Lynge, 1998;Burns et al, 2001;MacLennan et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…22,23,[25][26][27] However, these previous studies from pesticide manufacturing workers were based on few colorectal cancer cases. Our previous study from the Agricultural Health Study cohort 52 also did not support any significant association between alachlor exposure and colorectal cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…24 Elevated colorectal cancer risks have been observed in American cohorts of manufacturing workers exposed to the herbicide alachlor. [25][26][27] A study from Egypt reported that colorectal cancer patients had higher serum organochlorines levels than controls. 28 Other studies of farmers 29,30 and pesticide manufacturers, [31][32][33] however, did not show any excess risk of colorectal cancer.…”
mentioning
confidence: 99%
“…Lymphohematopoietic tumors were increased in one of these studies relative to expected values in the Iowa population (SIR = 3.6; 95% CI, 1.2-8.5) (Leet et al 1996); however, this estimate was based on only five exposed cases, and potential confounding factors were not included in the analyses. Two or fewer lymphohematopoietic cancer cases were available in studies conducted by Acquavella et al (1996Acquavella et al ( , 2004, and in general, none of the three studies of alachlor manufacturing workers provides strong evidence of an important relationship between alachlor and cancer. Studies of carbaryl and melanoma have not been conducted outside the AHS cohort, but Zheng et al (2001) reported an association between small-cell lymphoma among participants exposed to carbaryl in a pooled analysis of three case-control studies in the United States (Cantor et al 1992;Hoar et al 1986;Zahm et al 1990).…”
Section: Pesticidementioning
confidence: 99%